2021
DOI: 10.3390/app11031160
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of an NMC Battery for Application to Electric Light-Duty Commercial Vehicles and Comparison with a Sodium-Nickel-Chloride Battery

Abstract: This paper presents the results of an environmental assessment of a Nickel-Manganese-Cobalt (NMC) Lithium-ion traction battery for Battery Electric Light-Duty Commercial Vehicles (BEV-LDCV) used for urban and regional freight haulage. A cradle-to-grave Life Cycle Inventory (LCI) of NMC111 is provided, operation and end-of-life stages are included, and insight is also given into a Life Cycle Assessment of different NMC chemistries. The environmental impacts of the manufacturing stages of the NMC111 battery are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 41 publications
0
54
0
Order By: Relevance
“…Historically, LiCoO 2 and LiMn 2 O 4 have been used as cathode active materials in EV LIBs, although over the last decade there have been developments into different materials such as LiFePO 4 (LFP), LiNiCoAlO 2 (NCA) and LiNiMnCoO 2 (LiNMC), in which the ratios of nickel, manganese, and cobalt can vary depending on both the manufacturer and also within a manufacturer's fleet. 54,55 This variability in cathode chemistry will result in a waste stream that will have different LiNMC compositions, and it is likely that even in the future there will be mixed cathode chemistries needed to be recycled because of EoL car batteries being diverted into second life applications, or the continuance of EVs in the second hand car market. 56,57 While this variability in waste stream composition is likely to be problematic for the direct recycling of LIB cathodes, with the subsequent requirements for variable amounts of processing chemicals for each batch of electrodes, the ability to enrich a nickel-bearing phase is important because manufacturers are shifting towards the use of LiNMC-811 as the active cathode material.…”
Section: Proposed Flowsheetmentioning
confidence: 99%
“…Historically, LiCoO 2 and LiMn 2 O 4 have been used as cathode active materials in EV LIBs, although over the last decade there have been developments into different materials such as LiFePO 4 (LFP), LiNiCoAlO 2 (NCA) and LiNiMnCoO 2 (LiNMC), in which the ratios of nickel, manganese, and cobalt can vary depending on both the manufacturer and also within a manufacturer's fleet. 54,55 This variability in cathode chemistry will result in a waste stream that will have different LiNMC compositions, and it is likely that even in the future there will be mixed cathode chemistries needed to be recycled because of EoL car batteries being diverted into second life applications, or the continuance of EVs in the second hand car market. 56,57 While this variability in waste stream composition is likely to be problematic for the direct recycling of LIB cathodes, with the subsequent requirements for variable amounts of processing chemicals for each batch of electrodes, the ability to enrich a nickel-bearing phase is important because manufacturers are shifting towards the use of LiNMC-811 as the active cathode material.…”
Section: Proposed Flowsheetmentioning
confidence: 99%
“…Similarly, Accardo et al. ( 2021 ) had performed detailed LCA of NMC battery manufacturing and recycling processes. They have reported the life cycle inventory for electricity and natural gas required for manufacturing and recycling 1 kg battery pack.…”
Section: Model Parameterization and Scenario Descriptionmentioning
confidence: 99%
“…The process idea is to prevent lithium from being slagged and to recover it as a part of the gas phase instead. First trials, presented in [5], already showed that the amount of slag obtained is significantly lower than what should be expected from other pyrometallurgical processes [32,33]. However, it has not yet been proven if lithium can actually be removed via the gas phase.…”
Section: Introductionmentioning
confidence: 97%